Descrição da larva de último estádio de Micrathyria pseudeximia Westfall (Odonata, Libellulidae) - Dalzochio, Marina Schmidt (2009)
A larva de último estádio de Micrathyria pseudeximia Westfall, 1992 é descrita e ilustrada a partir de material procedente de Cascavel, Paraná, Brasil. A caracterização do gênero com base nas larvas é ampliada. Description of the Ultimate Stadium Larva of Micrathyria pseudeximia Westfall (Odonata, Libellulidae). Abstract. The larva of ultimate stadium of Micrathyria pseudeximia Westfall, 1992 is described and illustrated based on material collected in Cascavel Municipality, Paraná State, Brazil. The generic concept based on the larvae is amplified.